1997
DOI: 10.1159/000127247
|View full text |Cite
|
Sign up to set email alerts
|

Luteinising Hormone Secretion from the Perif used Ovine Pars tuberalis and Pars distalis: Effects of Gonadotropin-Releasing Hormone and Melatonin

Abstract: It is not known where melatonin acts to influence the neuroendocrine axis of seasonally breeding mammals. However, since the pars tuberalis (PT) contains the highest density of melatonin receptors, this adenohypophyseal subdivision is a potential target. Gonadotropes are the only immunocytochemically detectable adenohypophyseal cell type of abundance in the PT. This study investigated whether melatonin could modulate basal and/or gonadotropin-releasing hormone (GnRH)-stimulated luteinising hormone (LH) secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…In the experiment it was shown that melatonin reduced GnRH-induced LH release in the ovine PT explants. This result confirms the previously published data showing that melatonin may be involved in the suppression of LH release from ovine PTs [ 21 ]. Moreover, the modulatory action of melatonin on LH secretion was also determined in rodents—in male rats, melatonin inhibited GnRH-induced LH release from the PT -ME explants [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the experiment it was shown that melatonin reduced GnRH-induced LH release in the ovine PT explants. This result confirms the previously published data showing that melatonin may be involved in the suppression of LH release from ovine PTs [ 21 ]. Moreover, the modulatory action of melatonin on LH secretion was also determined in rodents—in male rats, melatonin inhibited GnRH-induced LH release from the PT -ME explants [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Melatonin receptors, however, are distributed over the entire pars tuberalis and extend into the zona tuberalis ( 14, 21, 24). Consistent with these observations, studies on perifused ovine pars tuberalis glands have shown that GnRH can induce LH release, and that melatonin can attenuate this effect ( 25). The inhibition of LH release by melatonin in response to a GnRH challenge does not occur in perifused ovine pars distalis ( 25), consistent with the distribution of melatonin receptors in the adult ovine pituitary.…”
Section: Melatonin and The Control Of Seasonal Reproductionmentioning
confidence: 73%
“…Consistent with these observations, studies on perifused ovine pars tuberalis glands have shown that GnRH can induce LH release, and that melatonin can attenuate this effect ( 25). The inhibition of LH release by melatonin in response to a GnRH challenge does not occur in perifused ovine pars distalis ( 25), consistent with the distribution of melatonin receptors in the adult ovine pituitary. The significance of these observations to seasonal reproduction is unclear, as the output of LH by the small number of gonadotrophs in the pars tuberalis is unlikely to have a significant impact on the circulating levels of LH, which will be dominated by the output from the pars distalis.…”
Section: Melatonin and The Control Of Seasonal Reproductionmentioning
confidence: 73%
“…The maintained expression of MT 1 in the PT of wild-type animals is probably largely attributable the presence of a population of PT-specific thyrotroph cells in this region that are insensitive to both GnRH and thyrotropin-releasing hormone (17,34,35); indeed, although Klosen and colleagues found LH␤ positive cells in the rat PT, they were unable to detect LH␤ coexpression with MT 1 (17). Although explant experiments suggest that a small population of gonadotroph cells may remain melatonin-sensitive within the PT in adults (38,41), the receptor subtype responsible for this phenomenon has not been defined.…”
Section: Discussionmentioning
confidence: 99%